INOVASI DAN MODERNISASI PENDIDIKAN PONDOK PESANTREN - Muhammad Hasan (Karsa: Journal of Social and Islamic Culture, 2015)
This article explores the meaning of innovation and modernization in the context of Islamic education in pesantren (Islamic boarding school). How are innovation and modernization model in boarding school at the moment? The study of innovation and modernization of islamic boarding school is important because it contains some important meanings; first, the study of innovation and modernization of pesantren is relevant in the context of Indonesia which is in the process of development and modernization; second, pesantren is a subculture of Indonesia islamic education so that in relation to innovation and modernization it will provide a unique color; Third, education in pesantren is a prototype of the ideal education model for Indonesia because it integrates cognitive, affective, and psychomotor domain. This paper concludes that the terms of both innovation and modernization relate to social change. The only difference is in the emphasis of characteristic of the change. Innovation emphasizes the traits being observed known as something new for individuals or communities, while modernization focuses on the process of change from traditional to modern, or from underdeveloped to a developed state. In the context of today's pesantren, there are at least three aspects involving in the modernization, innovation, and reform of the pesantren, namely the aspect of the method, content, and management.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.728